The Impact of Compensation Upon Employee Performance with Job Satisfaction as An Intervening Variable at the Dental Health Centre Jakarta Group - Winaningsih, Wiwin; Yustika, Iyus; Dewi, Sinta Maulina; Sulistiyowati, Lisa Harry; Maryam, Siti (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The objective of this research is to assess the impact of compensation upon employee impactiveness, while taking into account job contentment as an intervening factor, within the Dental Health Centre Group located in Jakarta. Design/methodology/approach: This research employs a quantitative methodology and utilizes primary data obtained from a purposively sampled group of 113 employees from the Dental Health Centre Group in Jakarta. The data analysis techniques involve validity testing, reliability testing, classical assumption testing, hypothesis testing utilizing t-tests and F-tests, as well as path analysis testing. Statistical Product and Service Solution (SPSS) Version 22 is utilized for the analysis. Findings: The outcomes suggest that compensation has an impact upon job contentment, albeit without any impact upon employee productivity. Nonetheless, job satisfaction has a significant bearing upon employee performance. It is noteworthy that the connection among compensation and employee performance is not entirely designed by job satisfaction. Practical implications: According to the research outcomes regarding the three variables, it is apparent that compensation has a significant impact upon job contentment, which in turn affects employee productivity. Consequently, it is suggested that organizations offer fair compensation to cultivate worker satisfaction, ultimately amplifying their performance. Originality/value: The researcher asserts that this research represents his original work and is the first of its kind utilized at the Dental Health Centre Group in Jakarta, bearing the title of the research under examination, with the exception of citations from select summaries included as references. Paper type: Research paper